d Question 1. Factorize pqr + qr 2 − pr 2 − r 3 | Job Exam Rare Mathematics (JEMrare) - Solved MCQs

Question 1. Factorize pqr + qr 2 − pr 2 − r 3

Question 1. Factorize  pqr+q r^{2}-pr^{2}-r^{3}

Factorization methods —


To factorize this expression we see that qr is common between first two terms and - r^{2} is common between the last two terms. So this expression can be dealt by taking commons out from respective pair of terms;

 pqr+q r^{2}-pr^{2}-r^{3}

=qr(p+r)-r ^{2}(p+r)

If we put brackets again for the sake of understanding we see it as;

=[qr(p+r)-r ^{2}(p+r)]

Now we can see that (p+r) is common here – taking it out, we get;

=(p+r)[qr-r ^{2}]

So, these are two factors of the expression uptill now;

Butif seen closely in the second factor viz [qr-r ^{2}], r is again a common to be found — take it out – we get;

=r(p+r)[q-r ]

So, finally r , (p+r) and (q-r) are three factors of the given expression.


You may submit a MCQ or maths problem with solution tips here in the comment box below! If you could not solve anyone, you may submit a MCQ or maths problem without solution as well. We will try our level best to solve it for you!

Your email address will not be published.

You may use these <abbr title="HyperText Markup Language">HTML</abbr> tags and attributes: <a href="" title=""> <abbr title=""> <acronym title=""> <b> <blockquote cite=""> <cite> <code> <del datetime=""> <em> <i> <q cite=""> <s> <strike> <strong>